Recent Evidence in Epigenomics and Proteomics Biomarkers for Early and Minimally Invasive Diagnosis of Alzheimer’s and Parkinson’s Diseases - Mayo, Sonia; Benito-León, Julián; Peña-Bautista, Carmen; Baquero, Miguel; Cháfer-Pericás, Consuelo (Current Neuropharmacology, 2021)
Background: Alzheimer’s (AD) and Parkinson’s diseases (PD) show deposits of improperly folded modified proteins. Protein expression mechanisms are involved since the early stages. Several studies evaluated epigenomics and proteomics profiles in these patients, with promising results. In general, they focused on early, specific, and minimally invasive biomarkers for the diagnosis and prognosis of AD and PD. Objectives: This review aimed at summarizing results to find the most reliable evidence in the field. Results: Among epigenomics studies, there is a focus on microRNAs (miRNAs) as candidate diagnostic biomarkers for AD or PD from blood samples like miR-342-3p, miR-107, miR-106a-5p, miR-106b- 5p, miR-195, and miR-19b. In addition, DNA methylation has been tested in a few works, obtaining significant differences in some genes (NCAPH2/LMF2 COASY, SPINT1, BDNFTREM1, TREM2, NPAS2, PDE4D), which could be useful for evaluating the disease progression as well as potential risk factors. Regarding proteomics, most of the studies were untargeted and used plasma or serum samples. In general, they highlighted the importance of coagulation, inflammation pathways, and oxidative stress. Among targeted studies, some proteins (phosphorylated tau, C reactive protein (CRP), interleukins, necrosis factors, transferrin, glial fibrillary acidic protein (GFAP), and neurofilaments) showed different plasma levels in AD and PD patients in comparison with healthy participants. Finally, a few studies have identified specific-AD and PD epigenetic and proteomic biomarkers (ApoE and oxidized DJ-1) in comparison with other similar pathologies. Conclusion: In general, there is a common lack of clinical validation of these potential biomarkers because of which its use in clinical practice is still limited.
Keywords: epigenomics